Pengaruh Kebiasaan Membaca Surah Pendek Terhadap Pembentukan Kepribadian Religius Anak Di TK. Putri Kembar Kec. Sosa Julu - Febrina Rizky Hasibuan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the influence of the habit of reading short surahs on the formation of children's religious personalities at the PUTRI TEMBAR Kindergarten, Kec. Sosa Julu. This research uses quantitative methods. The population used in this research was 110 people, while the sample was taken 20% of the population, namely 22 people.This research uses a quantitative approach with an experimental type of research. The research design used pre-experimental with a one group pretest-posttest design type. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out conditional tests, namely the normality test and homogeneity test. Test the hypothesis using the